Implementation Of Mobile Bimx System On Uma Kabuong Limo House Virtual Restoration - Muhd Arief Al Husaini (Institute of Computer Science (IOCS), 2021)
Indonesia has many potential heritage buildings, one of which is Uma Kabuong Limo in the Kampar district. The Uma Kabuong Limo building was damaged and restoration measures were needed. Conventional methods give rise to the potential availability of mobility of building data. This study aims to use BIMx mobile technology system as a restoration method that produces virtual simulations. This research is qualitative descriptive research with simulation and modeling research method, which utilizes technology in producing models and can simulate the building environment to be restored. The object of the research was the Nurdin family's Uma Kabuong Limo in Belimbing Island Village, Kampar Regency, Riau Province. The result of this study is to successfully build the Uma Kabuong Limo model and can be simulated in the BIMx application. The use of BIMx provides ease of the process and avoids mistakes in the decision-making of the restoration of the Uma Kabuong Limo building.